Draft Tenth Five Year Plan (2002 - 07) and Annual Plan (2002 - 03) Proposals Volume -1 Government of Manipur - Planning Commission (Planning Commission, 2002)
Manipur has a total area of 22,327 Sq. Km of which nine-tenth consists of hills and only one-tenth comprises the valley. It is one of the Border States in the northeastern part of the country having an international boundary of about 352 kms. long stretch of land with Myanmar on the east. It is bounded by Nagaland on the north, Assam on the west and Mizoram on the south. the state is land-locked and it does not have any waterways transport system to link with other states of the country. Roads constitute the most important transport system. The state has a population of 23.88 lakhs as per 2001 census as against the population of 18.31 lakhs as per 1991 census registering a growth rate of 30.02 % during 1991 - 2001 as against a growth rate of 29.29% during 1981 - 91 period. It has a lopsided population distribution with 59% people living in the valley and 41% thinly dispersed in the hill areas. the State is divided into two broad divisions namely, the hills and the valley
Government of Manipur Planning Department